The Reform of the European Union System of Own Resources – Challenges and Prospects - Nelly Popova (Finance, Accounting and Business Analysis, 2022)
The present article is devoted to the reform of the system of own resources undertaken in the context of adoption of the long-term EU budget for 2021-2027. Although the introduction of these reforms was a result of exceptional circumstances, the necessity to modernise the revenue side of the EU has been acknowledged for a long time. The changes in the system of own resources in 2021-2027 were driven mainly by the necessity to provide new sources of revenue to ensure the repayment of the debts incurred in relation to the post-pandemic recovery of the Member States. The second objective of the reforms was to diversify the revenue structure of the budget. The new instruments to finance the EU budget agreed by the Member States and the European Commission can be considered as “genuine” own resources since they are related to EU policy priorities. However, given the strong increase of EU expenditure after the pandemic and the imminent repayment of the common debt, the system of own resources faces important challenges.